Tomographic Ultrasound Imaging to Control the Placement of Tension-Free Transobturator Tape in Female Urinary Stress Incontinence. (16th August 2016) - Gräf, Charlotte M.; Kupec, Tomas; Stickeler, Elmar; Goecke, Tamme W.; Meinhold-Heerlein, Ivo; Najjari, Laila
Abstract : Purpose . The objective was to evaluate, by means of tomographic ultrasound imaging (TUI), the reliability of a novel approach for determining the position of the implanted tension-free transobturator tape (TOT). Furthermore, we analyzed the association between the position of the tape at rest and the subjective cure in stress incontinent women. Methods . This retrospective pilot study consists of 32 stress incontinent women, who underwent TOT procedure and routine sonographic control at day 1 postoperatively and at follow-up visit. TUI was applied on the resulting 4D volumes, thereby delivering 9 axial slices with a 4 mm interslice distance starting at the meatus urethrae internus in caudal direction. The reliability of the approach was tested by two examiners. Postoperative and follow-up ultrasound parameters of uncured and cured patients were analyzed. Result s. Measurements of the position of the TOT demonstrated high intraclass correlation coefficients. We found minor differences between sonographic parameters at day 1 postoperatively and at follow-up after a median period of 321 days. In cured patients, the position of the tape was measured in a more caudal position than in uncured patients. Conclusions . TUI can be a reliable method for determining the position of the tape. Further studies are needed to evaluate whether the postoperatively determined position can be used as an indicator of future subjective cure.